Study of a flexible antenna for intelligent transport system application - Zabri, Siti Normi; Mohd Salleh, Nurhashikin; Abu, Maisarah; Mohamad, Sarah Yasmin (Institute of Electrical and Electronics Engineers Inc., 2018)
—This paper presents flexible microstrip antenna designs that can be used for Intelligent Transportation System (ITS) operating at a frequency of 5.9 GHz. Designing the flexible antennas for ITS provides alternative to automotive industry to place the antennas at various shapes and conditions. Two antenna arrangements are introduced to produce two different radiation patterns; omnidirectional and directional. Both antenna arrangements consist of a radiating patch and a ground plane which were printed on different side of dielectric substrate. In order to identify a suitable substrate for ITS application, each antenna arrangement is designed on three different substrates. Numerical predictions of the performance parameter from six different antennas, are compared and used to investigate the antennas flexibility, where the antennas are bent towards a cylinder with different radius.